Embodying the Great Mother: Olga Fröbe's Spiritual Authority at Eranos - Sugden, Chloë (Approaching religion, 2025)
This article examines the trans-disciplinary œuvre and hosting activities of the Swiss-based artist and archivist, Olga Fröbe-Kapteyn (1881-1962), founder of the Eranos Conferences and creator of the Eranos Archive. Drawn from my doctoral project's findings, the text argues that Fröbe’s self-identification with the "Great Mother archetype" functioned as a strategy of feminine spiritual authority at Eranos - expressed through practices of conference-hosting, image curation, archiving and visionary art-making. Through unpublished correspondence, Eranos-Jahrbücher texts, and visual analyses of Fröbe's Visions drawings (1934-37) and "Great Mother" Archive images, Fröbe is situated within 1930s New Age esotericism. Drawing on religious studies concepts and art-historical methods, her "mythopoetic performance" of the Great Mother is interpreted as a mode of both institutional and visionary authority. Fröbe's opus exemplifies how fin-de-siècle women mobilised visionary experience and archetypal symbolism, constructing autonomous modes of spiritual and epistemic leadership within modernist intellectual cultures.